Relational Analysis of Knowledge and Adoption of Organic Farming Practices in Gujarat State - Rohan Sharma , N.B. Jadav , Sandeep Chouhan , S.R.K. Singh and Tushar Athare (Indian Journal of Extension Education, 2016)
Organic agriculture may be considered as a development vehicle for developing countries like India, in particular with thiscontext research study was undertaken for 180 farmers in capacity building of farmers through training on organicfarming practices in Surendranagar, Jamnagar and Rajkot district of Gujarat state. The results shows that majority oftrained and untrained farmers had medium level of knowledge and medium level of adoption about organic farmingpractices. Among all the variables education, extension participation, organic farming experience, localite cosmopolitevalue orientation, risk orientation, scientific orientation had positive and significant association with the knowledge andadoption of organic farming practices in both trained and untrained farmers. While in addition to this trained farmers' hadalso positive and significant association with social participation, innovativeness and mass media exposure, market oforganic produce and herd size.